Establishment of a 3-Dimensional Intestinal Cell Model to Simulate the Intestinal Mucosal Immune System for Food Allergy Investigations - Fu, Linglin; Lin, Wanglei; Wang, Chong; Wang, Yanbo (Frontiers in Immunology, 2022)
Food allergy is a worldwide food safety problem with increasing prevalence. Developing novel approaches for food allergy investigations is the basis for controlling food allergies. In this work, a 3-dimensional (3D) intestinal cell model was established to simulate the intestinal mucosal immune system. Gut epithelial cell line CMT93 was cultured in a transwell insert above dendritic cells (DCs) isolated from mouse spleen and stimulated by egg allergen ovalbumin (OVA), then the conditioned media of DCs was transferred to T cells isolated from mouse spleen. The allergy-related indexes of each cell type were determined by qPCR and flow cytometry. Then the TAZ gene was knocked down in the CMT93 cells and the role of the Hippo pathway in OVA-induced food allergy was investigated. The 3D intestinal cell model showed more significant and more specific allergic responses than conventional cell models and is more convenient to be manipulated than the mouse models. This model is an ideal tool for food allergy investigations and would facilitate studies in the field of intestinal mucosal immunity.